Exosome signalling in the kidney - Oosthuyzen, Wilna (The University of Edinburgh, 2016)
Urine contains exosomes originating from the circulation and all cells lining the urinary tract. Exosomes are a route of inter-cellular communication along the nephron potentially able to transfer of protein and/or RNA. It is not known whether this is a regulated process analogous to other cell-to-cell signalling systems. The aims of this study were to develop nanoparticle tracking analysis (NTA) as a technique to quantify exosomes in urine. Secondly, the hormonal regulation of exosome uptake in vitro and in vivo was investigated. Thirdly, exosome excretion in a central diabetes insipidus (DI) patient and a patient group after radiocontrast exposure was measured to investigate exosome excretion along the kidney in injury. Using the fluorescent capabilities of NTA, urinary exosomes were quantified in urine samples. NTA was able to detect changes in aquaporin 2 levels in vitro and in vivo. Storage conditions for human urinary exosomes were also optimised using NTA. A kidney cortical collecting duct cell line (CCDs) was used to model regulation of exosome uptake in vitro. CCDs were stimulated with desmopressin, a vasopressin analogue, and uptake of fluorescently-loaded or microRNA-loaded exosomes was measured. Desmopressin stimulated exosome uptake into collecting duct cells via V2 receptor stimulation. Intra-cellular uptake of exosomes was confirmed by microRNA specific mRNA down-regulation. Mechanistically, exosome uptake in response to desmopressin required cyclic AMP production, was mediated by clathrin-dependent endocytosis and was selective for exosomes from kidney tubular cells. In mice, fluorescently-loaded exosomes were systemically injected before and after administration of the V2 antagonist, tolvaptan, and urinary exosome excretion was measured. Basally, 2.5% of injected exosomes were recovered in urine; tolvaptan treatment resulted in a 5-fold increase. By combining antibodies to nephron segment-specific proteins with NTA we measured human urinary exosome excretion in central diabetes insipidus (DI) and after radiocontrast exposure (n=37). In DI, desmopressin reduced the excretion of exosomes derived from upstream glomerular and proximal tubule cells. In patients exposed to radiocontrast, urinary exosomes from the glomerulus were positively correlated with the tubular injury markers KIM- 1 and NGAL. These findings therefore show that tubular exosome uptake is a specific, hormonally regulated process that is reduced with injury. Physiologically, exosomes are a mechanism of inter-cellular communication; therapeutically, exosomes represent a novel vehicle by which RNA therapy could be targeted for the treatment of kidney disease.
Keywords: exosomes; kidney; signalling